YOSHLARNING FUQAROLIK TARBIYASIDA FUQAROLIK POZITSIYANING OʻRNI - Orınbetov, N.T. (SCIENCE and SOCIETY, 2024)
This article talks about the citizenship education of young people in our country, the role of the citizenship position in it, its problems, and foreign experiences.